THE POSITIONS OF ADVERBS OF MANNER IN NOVEL “BEAUTIFUL BOY” BY DAVID SHEFF - Nurjanah Nurjanah (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2014)
The aim of this research is to find out the positions of adverbs of manner. The source of the data is “Beautiful Boy” a novel by David Sheff. This research uses a qualitative method. The writer classifies the data concerning the positions of adverbs of manner (initial, mid and end positions). The results of the research show that adverbs of manner placed in mid position comprise 47.69% are in the first range. Adverbs of manner placed at end position comprise 43.07% are in the second range. Finally, adverbs of manner placed in initial positions comprise 9.23%.Key words: adverbs of manner, positions of adverbs of manner, novel